Impacts of flexible renewable hybrid system with electric vehicles considering economic reactive power management on microgrid voltage stability and operation - Huan Xie; Ihab Omar; Husam Rajab; Rishabh Chaturvedi; Abdullah Abed Hussein; Narinderjit Singh Sawaran Singh; Jaber M. Asiri; Nimesh Raj; Tannmay Gupta; Ahmad Alizadeh (Scientific Reports)
Abstract This article delves into the eco-friendly operation of a smart microgrid, highlighting its ability to maintain voltage security through a flexible renewable hybrid system. The framework incorporates wind and bio-waste energy sources to produce electricity, while leveraging electric vehicles as mobile storage units and flexibility resources. The hybrid system is also capable of managing reactive power. The design focuses on two core Objectives: minimizing operational costs and bolstering voltage security in the grid. To ensure these goals are met, several critical constraints are addressed, including the AC optimal dispatch model, security limitations of the smart microgrid, management of hybrid resources and storage operations, and restrictions related to system flexibility. A single-objective optimization approach uses weighted functions alongside a fuzzy decision-making method to achieve a compromised solution. Stochastic programming is applied to accurately account for uncertainties linked to renewable energy production, load fluctuations, energy pricing, and electric vehicle integration. The research stands out for introducing a multi-objective energy scheduling approach that combines a flexible-renewable hybrid system with the adaptability of electric vehicles and the operational capabilities of bio-waste systems. Numerical simulations emphasize the effectiveness of this design in improving both the technical performance and economic feasibility of smart microgrids and hybrid systems. Noteworthy findings reveal that mobile storage units can fully meet the flexibility requirements of the hybrid system. In comparison with conventional load flow studies, this optimized system delivers enhancements in voltage stability, economic efficiency, and operational capacity by approximately 20%, 33%-65%, and 41%, respectively.